Obedience or Resistance: Muslim Conception of Time as a Reaction to the Authoritarian Turkish Modernization - İsmail Çağlar (İnsan & Toplum)
While considerations of Turkish modernization become more varied through studies with a social historical perspective, the limited number of alternative readings of the relationship between religion, state, and society is remarkable. Taking this as a departure point, this study investigates the possibility of analyzing the essence and existence of the different kind of opposition practiced by the ulema and sufis during the single-party period. In mainstream literature, the ulema and sufis’ lack of reactive and communal agency against the modernizing reforms has been evaluated as pacifist or conformist. This study focuses on the relationship of these figures to tradition, their different understanding of time and reality, their struggle for dignity and social prestige, and claims that they ultimately form part of an agency and an opposition that is non-modern.